War Drums: A Retrospective Analysis of Post 9/11 Media and the Mis-education of the American Public - Justin W. Williams; Isabel Araiza; Matthew Eichler (Adult Education Research Conference, 2011)
This empirical research contributes to the critical analysis of media as a source of information and misinformation for adults; paying specific attention to the institutional nexus of political communication serving as a tool of the structural elite in bolstering an agenda contingent upon a mis-educated populous. The theoretical framework resides within the critical theory of media utilizing the propaganda model as a perspective analysis of the structural components of political communication. It adds to the continued critical analysis of media by scholars who assert that consumers of media are indeed bound to the ideological discourse as participants, and that to some degree they have the agency to realize the source of the dominant ideology; however, if they are media literate or obtain proper education they will possess or will develop within themselves the ability to reject the current messages maintaining the ideological status quo.
Keywords: adult education; Iraq war; political communication; propaganda model; ideological detoxification